STRATEGY OF CONCENTRATE FEED BUSINESS DEVELOPMENT AT CV. MULTI NISSA KENCANA IN STABAT DISTRICT, LANGKAT REGENCY, NORTH SUMATERA PROVINCE - Shyfa Maudia; Jamilah Jamilah; Sakral Hasby Puarada; Barmawi Barmawi; Suryadi Suryadi (Jurnal Mahasiswa Agribisnis, 2025)
CV. Multi Nissa Kencana is a company that produces concentrate feed which is located in Stabat District, Langkat Regency, North Sumatra Province. Sales of feed concentrates have experienced a decline in production in the last two years due to limited raw materials and raw material prices which are increasing from year to year. Apart from that, the increasing demand for feed concentrate creates opportunities for CV Multi Nissa Kencana, so a development strategy for the feed concentrate business is needed. This research aims to develop an appropriate development strategy for the feed concentrate business in CV. Multi Nissa Kencana. The research method used is descriptive qualitative. The data analysis used in this research is SWOT analysis. The results of the analysis show that the alternative development strategy is appropriate to be applied to the CV concentrate feed business. Multi Nissa Kencana uses an SO (Strength-Opportunity) strategy, namely by evaluating distribution performance and identifying areas that need to be improved by establishing partnerships with distributors, maintaining the quality of concentrate feed and increasing brand awareness by using various marketing channels.